Effect of the Hand-Omitted Tool Motion on mu Rhythm Suppression - Isoda, Kazuo; Sueyoshi, Kana; Ikeda, Yuki; Nishimura, Yuki; Hisanaga, Ichiro; Orlic, Stéphanie; Kim, Yeon-Kyu; Higuchi, Shigekazu (Frontiers in Human Neuroscience, 2016)
In the present study, we investigated the effect of the image of hands on mu rhythm suppression invoked by the observation of a series of tool-based actions in a goal-directed activity. The participants were 11 university students. As a source of visual stimuli to be used in the test, a video animation of the porcelain making process for museums was used. In order to elucidate the effect of hand imagery, the image of hands was omitted from the original ("hand image included") version of the animation to prepare another ("hand image omitted") version. The present study has demonstrated that, in individuals watching an instructive animation on the porcelain making process, the image of the porcelain maker's hands can activate the mirror neuron system (MNS). In observations of “tool included” clips, even the "hand image omitted" clip induced significant mu rhythm suppression in the right central area. These results suggest that visual observation of a tool-based action may be able to activate the MNS even in the absence of hand imagery.